G90(P) Research exposure for UK junior paediatric trainees. (27th April 2016) - Lythgoe, H; Price, V; Beresford, MW; Peak, M; Hawcutt, D
Abstract : Introduction: The importance of clinical research is well recognised internationally (1), and is a priority of the UK's Royal College of Paediatrics and Child Health (RCPCH) (2). The RCPCH provides a generic training curriculum outlining mandatory research competencies for those in the first 1–3 years of paediatric training (ST1-3s) (Table 1 ). It is unclear how these skills map onto aspirations of junior trainees, or research requirements in future job applications. Aim: To determine exposure to research amongst UK junior paediatric trainees. Methods: Paediatric trainees in seven UK deaneries were invited to complete an online survey exploring research experience in their training. Research requirements for 'Grid' (subspecialist training) applications and consultant paediatrician posts were reviewed and considered in the context of the survey results. Results: Fifty-two trainees responded, with an even distribution across the three training years. Eighty-nine percent of trainees considered themselves to have had minimal or no clinical research experience during their paediatric training. Although fifty-eight percent of trainees were aware of 'research in paediatrics' competencies in the curriculum, only eight percent knew what the competencies were. Trainees considered research experience an important part of training but found opportunities limited (Figure 1 ). Sixty-nine percent of trainees didn't know who to ask for advice and support. Reported barriers to research included research opportunities being aimed at more senior trainees (therefore excluding junior trainees); emphasis on service provision; opportunities relying on "word of mouth"; and inflexible training structures making it challenging to take time out for research. Research competencies and experience featured highly in both Grid and consultant person specifications, most listing at least some aspects as essential criteria. Nationally, reports such as "Turning the tide" (3) have started addressing changes that are needed to improve research training. Locally solutions need to be implemented, with dissemination of best practice nationally. Solutions could include regional/multiregional research training days, encouraging Good Clinical Practice training earlier in training, and identifying research support leads in each hospital to guide trainees and share opportunities. Conclusion: Junior paediatric trainees consider research important, but report little experience, leaving limited training time to gain the competencies required for Grid and consultant positions.